Coping with high-achieving transnationalist immigrant students: The experience of Israeli teachers - Eisikovits, Rivka A. (Teaching and teacher education, 2008)
Little attention has been paid to teacher attitudes toward high-achieving culturally diverse student groups. This in-depth study focuses on the experience of Israeli teachers who tell the story of a decade and a half of educational work with their highly motivated, academically successful immigrant students from the Former Soviet Union. The paper explores the differential effect of subject matter and seniority on teachers’ experience. It analyzes communication patterns between teachers and their high-achieving transnationalist immigrant students according to these parameters. Implications for the educational treatment of academic excellence among immigrant students in a globalized context are considered.